2018
DOI: 10.1080/10803548.2018.1475927
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the role of internal layout of magnetic field-generating equipment on workers’ exposure at power substations

Abstract: The research findings revealed that the most harmonious arrangement of equipment in an industrial unit plays a major role in reducing the exposure of workers to magnetic fields and ultimately increases the level of their health in the workplace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Computer vision syndrome has been documented to be dependent on screen time ( 15 , 16 ). In consistent with previous findings, our study demonstrated a moderate positive correlation between average screen time and the sum grade of computer vision syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Computer vision syndrome has been documented to be dependent on screen time ( 15 , 16 ). In consistent with previous findings, our study demonstrated a moderate positive correlation between average screen time and the sum grade of computer vision syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Grip strength is known as a simple, fast, reliable, and non-expensive index to evaluate the functionality of the upper extremity [ 2 5 ]. Moreover, grip strength has been considered as a noninvasive marker of overall muscular strength, muscle mass, nutritional status, and a predictor of cardiovascular and non-cardiovascular mortality, disability, and surgical complications [ 6 9 ]. Studies have shown that low handgrip strength (HGS) in children and adolescents is the sign of a poorer metabolic profile and nutritional status which on many occasions will result in obesity, low levels of fitness, and premature mortality in adulthood [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Existing research recognises the critical role played by the exposure of workers to electromagnetic fields [1]- [5]. At low frequency, the exposure to magnetic field has been shown to be related to adverse effects in circulation of currents within the body [6], [7].…”
Section: Introductionmentioning
confidence: 99%